A PMM2-CDG caused by an A108V mutation associated with a heterozygous 70 kilobases deletion case report - E. Lebredonchel; A. Riquet; D. Neut; F. Broly; G. Matthijs; A. Klein; F. Foulquier (BMC, 2022)
Abstract Background Congenital Disorders of Glycosylation (CDG) are a large group of inborn errors of metabolism with more than 140 different CDG types reported to date (1). The first characterized, PMM2-CDG, with an autosomal recessive transmission, is also the most frequent. The PMM2 gene encodes a phosphomannomutase. Here, a novel genetic variation causing PMM2-CDG is reported.  Case presentation We report the case of a French child, from healthy and unrelated parents, presenting congenital ataxia with hypotonia, hyperlaxity, inverted nipples, as well as altered coagulation parameters and liver function. Transferrin isoelectrofocusing revealed a typical type I CDG profile. Direct Sanger sequencing and quantitative PCR of PMM2 revealed a unique and novel genotype. On one allele, the patient was heterozygote with a known missense variant NM_000303.3(PMM2):c.323C > T, p.Ala108Val in exon 4. On the second allele, whole genome sequencing (WGS) indicated the presence of a novel heterozygous 70 kb deletion. Conclusion We report in the present paper the largest known heterozygous deletion of a PMM2 gene. The observation reveals the impact of a precise diagnostic on genetic counselling: by using WGS, an erroneous conclusion of homozygosity in the case of a relatively rare variant could be avoided, and an index patient with healthy and unrelated parents correctly identified.